Behavioral Biases in Financial Reporting: Examining the Impact of Overconfidence and Risk Aversion on Managerial Accounting Practices - Rahmadi, Zara Tania; Rimbano, Dheo (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study explores the influence of behavioral biases, specifically overconfidence and risk aversion, on managerial accounting practices, focusing on their impact on aggressive and conservative financial reporting. Using an online survey of 200 managerial-level respondents, data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that overconfidence significantly drives aggressive financial reporting, while risk aversion promotes conservative practices. Furthermore, the interaction between these biases moderates their effects, highlighting the complexity of managerial decision-making. The study contributes to behavioral accounting theory by integrating psychological insights and providing practical implications for improving financial reporting accuracy through bias mitigation strategies. Future research is encouraged to examine additional biases, cross-cultural contexts, and the influence of technological advancements on managerial practices.